Review of Allied Health Education: 5 - Perry, J. Warren; Mase, Darrel Jay, 1905-; Hamburg, Joseph (Book collections on Project MUSE., 2015)
Ferment and change best describe the health care scene today. Any semblance of stability and controlled evolution in this important area is over for the foreseeable future. Unanticipated and sudden shifts in priorities have occured because of society's concern with the excessive costs, limited access, and restrictive modes of delivery of care in this major industry. Volume 5 of this useful and popular series explores in depth a number of these contemporary issues and changes: geriatrics, prospective payment, rural health, health promotion, computerized education, accreditation, and curricular articulation. These original essays will be of interest and importance to all concerned with education in the health professions.